Subnational Foreign Trade Data in Latin America: Diagnostic, Challenges, and Technical Pathways - Redondo, Felipe Ramon de Britto; Silva Junior, Orlando da (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais do XL Simpósio Brasileiro de Bancos de Dados, 2025)
National foreign trade data (a country’s exports/imports) is widely available, but demand for the subnational level (states, municipalities) is growing. This brings volume and variety challenges, due to granularity and differing data handling across countries. This work analyzes the conditions of Latin American subnational foreign trade data to propose technical pathways for integration and standardization aimed at analytical uses. A layered minimal Lakehouse architecture, centered on Data Exploration and Understanding is employed, and case studies (Mexico and Uruguay) are presented. Findings reveal heterogeneity in data collection, compilation and dissemination, highlighting the need for harmonization to enable comparative analysis.